Inflation targets and expectational consistency in a model with a non-linear interest rule - Iwai Drumond, Carlos Eduardo; de Jesus, Cleiton Silva; Pereima, João Basilio (Brazilian Keynesian Review, 2019)
The aim of this paper is to develop a post-Keynesian macroeconomic model that takes into account a non-linearity in the interest rate rule. We assume that the monetary authority considers, in the practice of monetary policy, an interaction between inflation rates and the rate of capacity utilization, so that the sensitivity of the interest rate rule to the gap of inflation in relation to target varies according to the economic cycle. The macroeconomic policy framework proposed here allows the monetary authority to be sensitive to the inflation and to the output without, losing sight of the anchoring role of the inflation target.